Pressure assisted partial filling affinity capillary electrophoresis employed for determination of binding constants of human insulin hexamer complexes with serotonin, dopamine, arginine, and phenol - Šolínová, Veronika; Žáková, Lenka; Jiráček, Jiří; Kašička, Václav (Analytica chimica acta, 2019)
A new method, pressure assisted partial filling affinity capillary electrophoresis, has been developed to study noncovalent molecular interactions of the hexamer of human insulin (HI) with biologically relevant ligands, basic phenolic neurotransmitters serotonin and dopamine, basic amino acid arginine, and very weakly acidic phenol, in alkaline aqueous media. The apparent binding constants, Kb, of the HI-ligand complexes were determined from the dependence of the effective migration time changes of the above ligands on the variable zone lengths of HI hexamer dissolved in the background electrolyte (BGE) and hydrodynamically introduced into the bare fused silica capillary close to the UV detector. The strong cationic electroosmotic flow (EOF) in alkaline BGEs, 40/40 mM Tris/tricine, pH 8.1, and 25/34 mM NaOH/tricine, pH 8.5, with EOF mobilities 52.0 × 10-9 and 58.0 × 10-9 m2V-1s-1, respectively, was reduced by the hydrodynamic counter flow induced by external pressure at the outlet capillary end to avoid expulsion of HI zone out of the capillary and to allow HI interaction with both cationic and anionic ligands inside the capillary. The HI hexamer interactions with the above ligands were found to be weak to moderately strong, with Kb values in the range 385-1314 L mol-1, and decreasing in the order HI-phenol > HI-dopamine > HI-serotonin > HI-arginine.
Keywords: fenol; Serotonin; multimerizace proteinu; Insulin hexamer; Amino Acid Sequence; dopamin; Dopamine; vazba proteinů; Humans; sekvence aminokyselin; Ligands; Protein Multimerization; Partial filling; arginin; Electrophoresis, Capillary; elektroforéza kapilární; inzulin; serotonin; Protein Structure, Quaternary; Phenol; Human insulin; Affinity capillary electrophoresis; Arginine; Insulin; Neurotransmitters; tlak; Pressure; Binding constant; lidé; ligandy; kvarterní struktura proteinů; Protein Binding